Sosialisasi dan Edukasi Konversi Energi pada Kendaraan: Studi Komparatif Motor Listrik dan Mesin Konvensional bagi Pelajar Kejuruan - Jawwad, Jawwad Sulthon Habiby; Fifi Arisanti (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
The advancement of electric vehicle technology in the era of Industry 4.0 demands an increase in the competencies of vocational school teachers so they can effectively integrate relevant and up-to-date learning materials. This community service research aims to enhance teachers’ understanding and skills in delivering content that compares conventional engines and electric motors as part of the automotive engineering curriculum. The activity was carried out in the form of intensive training for vocational school teachers in the automotive field, using methods such as workshops, focused discussions, and hands-on practice based on modules specifically designed to meet technology-based curriculum needs. The results of the training show a significant improvement in the teachers’ understanding of the fundamental concepts of how conventional engines and electric motors work, as well as in their ability to develop learning strategies based on technological comparisons in the automotive field. These findings indicate that practical and technology-based training approaches can effectively improve teachers’ readiness to face teaching challenges in the digital transformation era. In conclusion, this training program positively contributes to strengthening both the pedagogical and technical capacities of vocational school teachers and supports the alignment of the curriculum with the ongoing development of modern automotive technology.